The Effect of Electronic Service Quality on Customer Satisfaction and Implications for LinkAja Customer Loyalty (Survey of Undergraduate Students of Class 2019, 2020, and 2021 of The Faculty of Economics and Business, Winaya Mukti University) - Hilman Abdurrahman; Nandan Limakrisna; Deden Komar Priatna (Dinasti International Journal of Management Science, 2024)
This research starts from the discovery of problems in low customer satisfaction which has an impact on customer loyalty. Low customer satisfaction is caused by low electronic service quality. This study aims to determine the effect of electronic service quality on customer satisfaction and its implications for LinkAja customer loyalty. The research method used is descriptive and verification method with a sample size of 80 respondents. Instrument testing uses validity and reliability tests. The data collection techniques used were observation and distributing questionnaires. The data analysis method used is path analysis, coefficient of determination analysis, and hypothesis testing. The results showed that in structure I there was an effect of electronic service quality on customer satisfaction of 78.6%, and the remaining 21.4% was influenced by other variables not studied. In structure II, there is an effect of customer satisfaction on customer loyalty of 40.2%, and the remaining 59.8% is influenced by other variables not studied. In structure III, there is an effect of electronic service quality on customer loyalty of 42.9%, and the remaining 57.1% is influenced by other variables not studied.